Development and cognitive testing of a food frequency questionnaire to assess intake of plant-based protein foods among older adults - Virginie Drolet-Labelle; Alexandra Bédard; Simone Lemieux; Vicky Drapeau; Lana Vanderlee; Danielle Laurin; Sophie Desroches
ABSTRACT Objectives: To develop a web-based food frequency questionnaire (FFQ) measuring intake of plant-based protein foods (PBPs) among older adults from the province of Quebec, Canada. Design: The questionnaire was adapted from an existing self-administered FFQ and first underwent expert panel evaluation for face and content validity. Then, three phases of cognitive testing were conducted in French, using the probe and think aloud approaches. Between each phase, the questionnaire was modified based on participants' feedback to improve the clarity and comprehension of the questions. Setting: Quebec City, Quebec, Canada. Participants: Twenty adults aged 65 years and older. Purposive sampling was used to maximize variation in sociodemographic characteristics, including gender, age, education level, and PBP consumption. Results: The expert panel found the 28-item questionnaire to be a comprehensive measure of PBP intake and suggested minor changes to improve its clarity. The cognitive interviews showed that our PBP-FFQ was generally well understood and identified issues requiring modifications to improve comprehension and accuracy. Discussion: Our FFQ provides a comprehensive measure of PBP intake, is well understood by older adults in Québec, and will support rigorous assessment of PBP intake in this population, but requires further validation to confirm validity and reproducibility.